Modern weapons and military equipment for the issue 2-2021 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Tank dreams: Mulling the future of Russian armour design concepts Elta Systems reveals new passive radar Rafael demos Drone Dome-L with hard-kill laser capability Eyes in the sky: How the Orlan-10 UAV is shaping Russian artillery operations EDA readies smart textile for operational testing Russian army to get Sprut-SDM1 SPATG self-propelled anti-tank gun